Degenerate four-wave mixing studies of butadiyne-linked conjugated porphyrin oligomers - Thorne, J; Kuebler, S; Denning, R; Blake, I; Taylor, P; Anderson, H (1999)
The third-order electronic susceptibilities have been measured in solution for a series of conjugated porphyrin oligomers, and for a conjugated polymer of this type. At 1064 nm, the non-resonant susceptibilities of the oligomers and the polymer are large (χ (3)≈10 -17-10 -16 m 2 V -2), have comparable real and imaginary parts, and the real part is negative in sign. The molecular susceptibility per ring chromophore, (γ/N), shows a linear dependence upon chain length, N. We propose a general mechanism for the enhancement of the third-order susceptibilities in conjugated porphyrin based materials due to two-photon resonance with charge transfer states.